The Influence of Competence, Work Environment, and Work Facilities on ASN Performance at the Lolayan Sub-District Office - Mangundap, Ferawaty (Universitas Sebelas Maret, 2026)
This study examines the influence of competence, work environment, and work facilities on the performance of ASN (Civil Servants) at the Lolayan Sub-District Office, Bolaang Mongondow Regency, North Sulawesi. ASN performance is a critical element in delivering effective public services at the sub-district level and requires support from competent human resources, a conducive work environment, and adequate facilities. This research employs a quantitative approach with an associative design. The study was conducted within a single sub-district office with a relatively small population of 34 ASN. Given this limited institutional scope, the findings are contextual in nature and cannot be generalized broadly to other organizations with different characteristics. A total of 33 respondents were selected using a saturated sampling technique. Data were collected through a Likert-scale questionnaire developed based on established indicators for each variable. Multiple linear regression analysis was performed using IBM SPSS version 26. The results show that competence and work environment have a positive and significant effect on ASN performance, whereas work facilities have a negative and non-significant effect (t = -0.887; p = 0.382). The negative coefficient reflects a statistical tendency within the regression model and does not indicate an actual negative relationship. Simultaneously, competence, work environment, and work facilities have a significant effect on ASN performance, with competence emerging as the most dominant factor (β = 0.609). These findings offer practical implications for strengthening ASN performance through competence development and a supportive work environment.